The symbolic consumption and identity construction through luxury branded clothing among Rhodes University students - Chinomona, Perpetua (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
The purpose of this study is to explore how Rhodes University (RU) students construct identity through the symbolic consumption of luxury branded clothing and the role played by reference groups in the consumption behaviour. The study employed the Social Identity Theory (SIT) as a theoretical framework which explains the underpinnings of the cognitions and behaviour with the use of group processes (Trepte, 2006). The central principle of SIT lies in individuals classifying themselves and others into in-group (reference groups) and out-group social categories respectively. There has been a gap in the literature pertaining to a full understanding of the identity construction process through symbolic consumption of luxury brands in South Africa (Reed, 2002). The significance of the study is to provide a foundation for an enhanced theory of consumer behaviour in this context. This study employed a qualitative research approach. A non-probability convenience sampling technique was used, and a total of 12 undergraduate and postgraduate students were interviewed. The chosen data collection method was semi-structured in-depth interviews and data were analysed using thematic analysis. The findings of the study revealed that participants consume luxury branded clothing for both functional and symbolic purposes. Various factors emerged that influence the choice of the symbolic consumption behaviour such as income, buying frequency, spending patterns, perceptions and habits around retail shopping and the shopping experience. In addition, results indicated that reference groups (celebrities, family and peers) play a significant role in the symbolic consumption and construction of identity among the participants. In addition, the results also indicated that the RU participants engaged in a 'save to spend' technique whereby they save their pocket money so that they spend it on their favourite luxury branded clothing when they leave for the holidays. There was a common reference group that emerged from the study, namely the peer in-group. The influence of reference groups on youth consumers in South Africa may assist with marketing strategies that can be employed when targeting the Generation Y. Additionally, results indicate that luxury branded clothing have an impact on identity construction within the South African context. The respondents tie their identity to their luxury branded clothing as an indication of 'who they are' and as an extension of the 'self'.
Keywords: Group identity; Peer pressure; Brand choice -- South Africa -- Makhanda; Consumer behavior -- South Africa -- Makhanda; Consumer behavior -- Psychological aspects -- South Africa -- Makhanda; Luxuries -- Psychological aspects -- South Africa -- Makhanda; Rhodes University -- Students -- Attitudes